Unique distribution of aromatase in the human brain: in vivo studies with PET and [N-methyl-(11)C]vorozole - Biegon, Anat (2010)
Aromatase catalyzes the last step in estrogen biosynthesis. Brain aromatase is involved in diverse neurophysiological and behavioral functions including sexual behavior, aggression, cognition and neuroprotection. Using positron emission tomography (PET) with the radiolabeled aromatase inhibitor [N-methyl-(11)C]vorozole, we characterized the tracer distribution and kinetics in the living human brain. Six young, healthy subjects, 3 men and 3 women, were administered the radiotracer alone on two separate occasions. Women were scanned in distinct phases of the menstrual cycle. Specificity was confirmed by pretreatment with a pharmacological (2.5mg) dose of the aromatase inhibitor letrozole. PET data were acquired over a 90 min period and regions of interest placed over selected brain regions. Brain and plasma time activity curves, corrected for metabolites, were used to derive kinetic parameters. Distribution volume (VT) values in both men and women followed the rank order: thalamus>amygdala=preoptic area>medulla(inferior olive) > accumbens, pons, occipital and temporal cortex, putamen, cerebellum and white matter. Pretreatment with letrozole reduced VT in all regions, though the size of the reduction was region dependent; ranging from ~70% blocking in thalamus and preoptic area to ~10% in cerebellum. The high levels of aromatase in thalamus and medulla (inferior olive) appear to be unique to humans. These studies set the stage for the non-invasive assessment of aromatase involvement in various physiological and pathological processes affecting the human brain.